Increased Moisture Uptake of NCM622 Cathodes after Calendering due to Particle Breakage. Issue 9 (20th September 2021) - Huttner, Fabienne; Diener, Alexander; Heckmann, Thilo; Eser, Jochen C.; Abali, Tugay; Mayer, Julian K.; Scharfer, Philip; Schabel, Wilhelm; Kwade, Arno
Abstract : As moisture presents a critical contamination in lithium-ion batteries (LIBs), electrodes and separators need to be post-dried before cell assembly. The moisture adsorption, desorption and re-adsorption of electrodes during processing is strongly dependent on their material system, manufacturing route and microstructure. The microstructure, in turn, is significantly defined by the coating density, which is adjusted by calendering. As a consequence, the calendering step is expected to directly influence the moisture sorption behavior of electrodes. This is why the influence of different coating densities and structural properties on the moisture content of NCM622 cathodes was investigated in this study. For increasing density, an increasing moisture content was detected by Karl Fischer Titration and sorption measurements. SEM and BET analyses showed an increasing amount of NCM622 particle breakage, accompanied by a rising surface area. Hence, the increased moisture uptake of cathodes with higher density is mainly caused by a higher surface area, which results from particle cracking and breakage during calendering. Electrochemical analysis showed that the increased active surface area of cathodes with higher densities leads to a good performance during formation and at low C-rates. However, the reduced porosity impairs the ionic conductivity and causes capacity loss at higher C-rates.